Fifteen years of Poland's membership of the European Union: Poland's participation in the internal market for services - Alina Szypulewska-Porczyńska; Magdalena Suska (International Journal of Management and Economics, 2020)
The purpose of this article is to examine the changes that have occurred after Poland's integration into the European Union (EU) internal market for services after 2004 considering the legal changes adopted in the EU relating to the free movement of services, namely, the Service Directive. An examination of the Directive's outcome and the development of the market integration process permit the conclusion that the changes in regulatory trade barriers have had a relatively limited impact on the changes that have occurred in EU-Polish ties concerning services trade. These were predominantly shaped by structural and macroeconomic factors. From an analysis of the structure of Poland's services trade, a picture emerges of a deepening asymmetry between the exports and imports sides of Poland's participation in the internal market.
Keywords: F1; 650; Services Directive; Poland; EU; integration; trade in services